Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan dengan Turnover Intention sebagai Variabel Intervening - Susanti, Susanti; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2016)
The purpose ofthis study is to know the influence of job satisfaction, organizational commitment, and turnover intention on employees’ performance directly and indirectly that is mediated by turnover intention. The population in this study is the Custom employees of PT Milan Indonesia numbering to 444 employees. The samples that are used in this study are 82 employees using formula of Slovin.The method of data collection is by quesionares measured with likert scale.Data analysis using percentage descriptive, partial multiple regression analysis and path analysis using SPSS for Windows version 16. Based on the result hypothesis test, then the conclusion are job satisfaction and organizational commitment gives negatif effect and significant on turnover intention. Job satisfaction and organizational commitment gives positif effect and significant on employee performance and turnover intention gives negatif effect and significant on employee performance. Turnover intention has mediate the relationship between job satisfaction and organizational commitment on employee performance.